Endovascular treatment of intracranial aneurysms using the Pipeline Flex embolization device: a case series of 30 consecutive patients. (13th March 2015) - Martínez-Galdámez, M; Pérez, S; Vega, A; Ruiz, P; Caniego, J L; Bárcena, E; Saura, P; Méndez, J C; Delgado, F; Ortega-Gutierrez, S; Romance, A; Diaz, T; et al.
Abstract : Background: The Pipeline Flex embolization device has some peculiarities in comparison with the previous generation device. Despite recent reports of the modified delivery system, its safety is still unknown. Objective: To illustrate the intraprocedural and periprocedural complication rate with this new device in 30 consecutive patients. Material and methods: Clinical, procedural, and angiographic data, including aneurysm size and location, device or devices used, angiographic and clinical data were analyzed. Results: 30 patients harboring 30 aneurysms were analyzed. 39 devices were placed properly. Multiple Pipeline embolization devices (PEDs) were used in 7 cases. In 28 devices the distal end opened fully from the beginning with a complete wall apposition. In the remaining 11 devices, distal-end opening of the devices was instant but partial, but fully opened easily after recapture. Among the 30 procedures, recapture and reposition of the Pipeline Flex was performed four times owing to proximal migration/malposition of the device during delivery. Four intraprocedural/periprocedural complications occurred, of which 2 resulted in major complications, with neurologic deficits persisting for longer than 7 days. The 30-day morbidity rate was 6.6%, with no deaths. No aneurysm rupture or parenchymal hemorrhage was seen. Conclusions: The Pipeline Flex embolization device allows more precise and controlled deployment than the first-generation device. The number of devices and the complication rate during the learning curve are lower than reported with the first-generation PED. The new delivery system and the resheathing maneuvers do not seem to increase the intraprocedural complication rate in comparison with the first-generation PED.